URINARY BIOMARKERS FOR FOLLOW-UP OF RENAL TRANSPLANTATION - WHERE WE ARE! - Goran Nikolov; Margaritka Boncheva; Todor Gruev; Katerina T. Trajkovska; Irena Kostovska (Peytchinski Publishing Ltd., 2016)
Early diagnosis of renal allograft dysfunction is crucial for the management and long-term survival of the transplanted kidney. Early after transplantation, acute tubular necrosis (ATN) manifesting as delay graft function (DGF) or slow graft function, acute rejection (AR) or drug toxicity (e.g. calcineurin inhibitor) are the leading causes of Acute kidney injury (AKI). Acute rejection, ATN, and calcineurin inhibitor toxicity continue to be major causes of renal allograft dysfunction along with other causes like infections (e.g. BK and CMV viruses, pyelonephritis), obstruction, and recurrence of the original disease. Clinicians have been searching for non-invasive tools that would allow the diagnosis of acute renal allograft dysfunction early and accurately without performing a kidney biopsy. The following comprehensive review will describe the latest findings on urinary biomarkers in acute allograft dysfunction.
Keywords: acute kidney injury (AKI); urinary biomarkers; renal transplantation